Contemporary Australian socio‐cultural factors and their influence on medical student rural career intent. (5th April 2022) - Padley, James; Gonzalez‐Chica, David; Worley, Paul; Morgan, Katrina; Walters, Lucie
Abstract: Objective: To understand how contemporary socio‐cultural factors may impact medical students' rural career intent. Design: Cross‐sectional study using data from the national Federation of Rural Australian Medical Educators survey. Participants/setting: Medical students across 18 Australian universities who completed a full academic year of clinical training in rural areas in 2019. Main outcome measure(s): Preferred location of practice post‐training reported to be either: (i) a major city; (ii) a regional area or large town; or (iii) a small rural location. Results: In total, 626 students completed the survey (70.1% response rate). A small rural location was the most preferred location of practice after graduation for 28.3% of the students (95% CI 21.6–36.0). Four socio‐cultural factors were positively associated with a preference for a rural career location: poor health status of rural people, motor vehicle traffic congestion in cities, rural generalist training opportunities in the state and the Royal Flying Doctor Service. Other socio‐cultural factors, including specialists' under‐employment, Medicare freeze effect on doctors' income, bullying/sexual harassment in hospitals, climate change/natural disasters or recognised rural health personalities did not influence the investigated outcome. Conclusions: Our findings indicate a novel association between contemporary socio‐cultural factors and rural career intention in a cohort of Australian rural clinical school students. These findings advocate for further consideration of research exploring socio‐cultural factors shaping rural career intent and workforce outcomes.